UNEXPECTED FOREIGN BODY AS A REASON OF LOBAR PNEUMONIA IN A 6,5 YEARS OLD BOY – CASE REPORT - Mitrovska Josifova, Veselinka; Boskovska, Katerina; Chakalaroska, Irena; Arnaudova Danevska, Ivana; Spasova, Olga; Ivanovska, Julija; Fidanoska Jovicic, Vesna; Buzarov, Jane (Journal of Morphological Sciences; Vol 5 No 3 (2022): JMS, 2022)
We present a case of a foreign body as a reason for right lobar pneumonia in 6,5 years old boy. He was admitted in our hospital because of 6 day high fever (up to 40 CÍ¦ ), malaise, cough, stomach ache. Clinically he had impaired breathing in the basis of the right lung, and laboratory findings were with elevated inflammatory markers. The radiogram of the chest showed round consolidation in the right low lung lobus.  Microbiologicaly, we isolated Mycoplasma pneumonia (IgM) from pneumoslide, and also Staphylococcus aureus â€“ MRSA from the sputum. Additional immunology tests like immunoelectrophoresis ( IgA, IgG, IgM) were done, all of them with results in normal ranges.  After one week of therapy with parenteral rehydration, wide spectral antibiotics (according to antibiogram), inhalatory  bronchodilatator and systemic corticosteroid, the child presented with scarce haemoptysis, with consecutive clear haemoptysis on the 10-th day. This set for bronchoscopy and Mx-test with PPD5, which was negative. Flexibile bronchoscopy was made at 11 th day of the stay, with visualized foreign body- grass like structure in the openings of the arm of middle and lower right bronchus. We continued with rigid bronchoscopy, with successfully removed grass- Hordeum murinum. After the intervention we observed completely clinical recovery of the lung findings, as well as radiological improvement Key words: bronchoscopy, foreign body, Hordeum murinum.